An introduction to the New Testament and the origins of Christianity - Burkett, Delbert Royce. (Cambridge University Press, 2002)
This book offers an authoritative and accessible introduction to the New Testament and early Christian literature for all students of the Bible and anyone interested in the origins of Christianity. It is designed primarily for undergraduate courses in the New Testament, biblical studies and early Christianity. There are questions for in-class discussion and written assignment, step-by-step reading guides on individual works, special box features, charts, maps and numerous illustrations designed to facilitate student use. With this textbook and the Bible, the student should therefore have all the necessary basic texts.